MEMAHAMI DAN MENGELOLA DAMPAK PARIWISATA - Victor Bangun Mulia (JURNAL KEPARIWISATAAN, 2021)
This paper aims at providing information and understanding about the impacts of tourism on the economic sector, sociocultural living, and environmental. Globally, tourism is considered as one of the leading sectors contributing huge numbers in the global GDP. Now wander many countries rely on the tourism sector as the source of income and many countries do their best to develop the tourism potency had. The rapid dan massive development of tourism in the world brings both negative and positive aspect to those three sectors; economic, socio-cultural, and environmental. The negative impacts of tourism should be anticipated and managed well by the government, stakeholder, and community. One thing that can be done is by implementing visitor management that is an administrative action to maintain the environment, socio-cultural living, and economic sector without neglecting the satisfaction of tourists. Visitor management is implemented by balancing the tourist’ needs, local community’s needs, stakeholders’ needs, and the current situation and potency of the destination. The implementation visitor management leads to the sustainable tourism.